Ethical Leadership, Compensation, and Culture and Employee Performance: Census Sampling Approach - Niki Puspita Sari; Helmi Muhammad; Eko Satya Aliansyah (Universitas Muhammadiyah Sidoarjo, 2022)
This study analyzes the effect of ethical leadership, compensation, and organizational culture on employee performance. This research is quantitative with a sample of 42 employees through the census method. The multiple linear regression analysis showed several results. First, ethical leadership has no significant effect on employee performance. Second, compensation has a significant impact on employee performance. Third, organizational culture has a significant negative impact on employee performance. Although the results contradict previous studies, ethical leadership, compensation, and organizational culture still have an essential role in achieving employee performance. The results provide positive implications for improving employee performance through applying for compensation and work culture. However, the implementation of work culture needs to be accompanied by other variables such as good corporate governance.